(untitled) (Bangladesh Journal of Microbiology, 2011)
Bacterial numbers in surface water samples, collected randomly from six different water bodies, were estimated by acridine orange direct counting (AODC) and conventional culture-based heterotrophic plate counting (HPC). Bacterial genomic DNA was prepared from water samples by employing methods used for stool samples, including the population dynamics, were determined by primer extension of the 16S rDNA (V6/V8 region) using polymerase chain reaction (PCR), followed by denaturing gradient gel electrophoresis (DGGE), a metagenomic tool that is capable of separating unrelated DNAs based on the differences in their sequences and GC contents. The bacterial numbers in water samples ranged from 103 – 106 CFU/ mL for HPC and 104 – 107 cells/ mL for AODC, showing that a great majority of bacteria prevail as uncultivable which do not respond to culture methods that are used widely for tracking bacterial pathogens. The acridine orange-stained bacteria varied in sizes and shapes, and appeared either as planktonic (solitary) cells or as clusters of biofilms, showing the presence of diverse community under the epifluorescence microscope. The DGGE of the ca. 457 bp amplicons, as confirmed by agarose gel electrophoresis, produced bands that ranged in intensities and numbers from 18 to 31, with each band possibly indicating the presence of one or more closely related bacterial species. The enrichment of pathogenic bacteria in the aquatic ecosystem is known to precede the seasonal diarrhoeal outbreaks; therefore, bacterial community dynamics determined by Metagenomic 16S PCR-DGGE during pre-epidemic enrichment appears promising in predicting the upcoming diarrheal outbreaks. Key words: Metagenomics; 16S rDNA; PCR; DGGE; bacterial community dynamics DOI: http://dx.doi.org/10.3329/bjm.v27i2.9171 BJM 2010; 27(2): 46-50